A Review of Social Media Marketing Strategies impacting Women’s buying behavior (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This review explores the profound influence of social media marketing strategies on women’s purchasing decisions. In recent years, the proliferation of social media platforms has transformed consumer behavior, particularly among female demographics. This study analyzes various strategies employed by brands to engage and persuade women through social media channels.The research highlights the necessity of directed advertising that is specifically crafted to cater to the interests and preferences of women. In order to properly match products with the varied requirements of female consumers, brands make use of advanced algorithms to provide tailored information. In addition, influencer marketing has emerged as a crucial tactic, which involves the honest endorsement of items by personalities who are easily relevant. This helps to cultivate trust and encourages consumers to make purchases.The study also investigates the influence that user-generated content (UGC) has on the buying behavior of women. In order to harness the power of peer recommendations, which have a substantial impact on purchase decisions, brands should encourage customers to share their experiences with products through postings and reviews. Authenticity and relatability are two characteristics that appeal powerfully with female customers, and the impact of user-generated content (UGC) often surpasses that of traditional marketing tactics.In conclusion, this analysis highlights the transforming impact that social media marketing strategies have on the buying behavior of women. By adopting targeted advertising, influencer collaborations, community participation, and user-generated content, brands have the ability to successfully connect with female customers, which in turn drives purchase choices and fosters long-term brand loyalty.